Cultural Roots of Entrepreneurship: Evidence from Second-Generation Immigrants - Kleinhempel, Johannes; Klasing, Mariko J.; Beugelsdijk, Sjoerd (Organization Science, 2023)
Does national culture influence entrepreneurship? Given that entrepreneurship and the economic, formal institutional, and cultural characteristics of nations are deeply intertwined and co-vary, it is difficult to isolate the effect of culture on entrepreneurship. In this study, we examine the self-employment choices of second-generation immigrants who were born, educated, and currently live in one country, but were raised by parents stemming from another country. We argue that entrepreneurship is influenced by durable, portable, and intergenerationally transmitted cultural imprints such that second-generation immigrants are more likely to become entrepreneurs if their parents originate from countries characterized by a strong entrepreneurial culture. Our multilevel analysis of two independent samples—65,323 second-generation immigrants of 52 different ancestries who were born, were raised, and live in the United States and 4,165 second-generation immigrants of 31 ancestries in Europe—shows that entrepreneurial culture is positively associated with the likelihood that individuals are entrepreneurs. Our results are robust to alternative non-cultural explanations, such as differences in resource holdings, labor market discrimination, and direct parent-child linkages. Overall, our study highlights the durability, portability, and intergenerational transmission of entrepreneurial culture as well as the profound impact of national culture on entrepreneurship. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1645 .